Microstructure and thermoelectric properties of Al-doped ZnO ceramic prepared by spark plasma sintering. Issue 3 (March 2023) - Radingoana, Precious Manti; Guillemet-Fritsch, Sophie; Noudem, Jacques; Olubambi, Peter Apata; Chevallier, Geoffroy; Estournès, Claude
Abstract: The high thermal and low electrical conductivities of ZnO ceramics have hindered their thermoelectric applications. The doping of ZnO with group 3 elements can enhance the thermoelectric properties. In this work, Al (2 at%) doped ZnO powder was sintered using spark plasma sintering at varying parameters (such as temperature (550–700 ℃), pressure (250–500 MPa) and the temperature of pressure application (Room Temperature (RT) and Holding Time (HT))). Maximum relative density of 98.9% was achieved at a temperature and pressure of 650 °C and 250 MPa, respectively. The Al-doped ZnO ceramics improved in electrical conductivity which caused a decrease in the Seebeck coefficient because of increased carrier concentration. The reduction in the grain size due to inhibiting growth effects of aluminum lead to a decrease in the thermal conductivity through phonon scattering at the grain boundaries. Hence, ZT of 0016 at 500 °C was obtained. This study indicated that Al-doped ZnO ceramics can be sintered at very low temperature of 650 °C. These conditions allow to retain the nanostructure, which is beneficial in improving the thermoelectric properties.